Association of Sleep Apnea With Development and Behavior in Down Syndrome: A Prospective Clinical and Polysomnographic Study - Anand, Vaishakh; Shukla, Garima; Gupta, Neerja; Gupta, Anupama; Sapra, Savita; Gulati, Sheffali; Pandey, Ravindra Mohan; Pandey, Shivam; Kabra, Madhulika (Pediatric neurology, 2021)
The prevalence of sleep-disordered breathing is high in children with Down syndrome. Although the association between sleep-disordered breathing and developmental delay and behavioral abnormalities are proven among typically developing children, there are few such studies of children with Down syndrome. This study assesses the relationship between the severity of sleep apnea and development and behavioral abnormalities in individuals with Down syndrome. In a cross-sectional prospective study, 53 children with Down syndrome were assessed for sleep-disordered breathing by overnight polysomnography. Behavior was assessed using Child Behavior Checklist (CBCL) and developmental quotient (DQ) using Developmental Profile 3. The association between various domains of behavior and development with the Apnea-Hypopnea Index (AHI) was assessed using Spearman rank correlation. Multiple linear regression assessed the independent effects of various factors on development and behavior. Of 53 subjects (three to 11.8 years), 51 (96%) were found to have obstructive sleep apnea (OSA). In both three to five year and six to 12 year age groups, there was a statistically significant positive correlation between the CBCL scores and the AHI (rho = 0.77 and 0.83, respectively). There was a statistically significant negative correlation between the DQ and the AHI (rho = −0.62). In multiple linear regression, AHI was the only independent variable that was associated with CBCL and DQ. This study provides robust evidence that OSA can negatively influence the development and behavior in children with Down syndrome as in typically developing children. Moreover, with increasing severity of OSA, children with Down syndrome have more behavioral abnormalities, especially attention deficit and hyperactivity, and also have poorer development scores.